Biological peculiarities of seed germination of Ukrainian flora rare orchids to create a backup of genetic collections - Sheyko, O. A.; Sherbatiuk, M. M.; Krupa, N. M.; Kosakivska, I. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Some biological characteristics of seedbreeding, which reveal a significant heterogeneity of seeds of wild species of orchids of the Ukrainian flora, are investigated. Analysis of the fruit formation rate coefficient for 2012–2014 shows a close dependence on the environmental conditions. Morphological analysis of seed shows that, in the investigated species of orchids at the time of dissemination, most of the seeds were unviable. The data suggest that the most successful species for the reintroduction are D. incarnata, C. longifolia, and N. nidus-avis, since the species are characterized by the largest proportion of viable seeds from the relatively large size of embryos.